Pengembangan Jiwa Wirausaha Lulusan Teknik Elektronika SMK N 1 Bukittinggi Melalui Pembekalan Skill Pembuatan Game dengan Unity - Aldo, Dasril; Sahara, Sahara; Ilmi, Miftahul (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: The gaming industry offers substantial opportunities for individuals with the right technical and entrepreneurial skills. However, graduates from vocational schools often lack these essential skills. Objective: The purpose of this service was to enhance technical skills in game development using Unity and cultivate entrepreneurial spirit among graduates of the Electronics Engineering Department at SMK N 1 Bukittinggi. Method: This public service was conducted on April 25, 2024, via Google Meet, in collaboration with Institut Teknologi Telkom Purwokerto, Universitas Jambi, and Institut Teknologi dan Bisnis Indobaru Nasional. The program included sessions on the basics of game development, practical game creation using Unity, and entrepreneurship training. Forty students participated. Result: The program significantly improved participants' skills. Understanding of game development theory increased from 30% to 85%, proficiency in using Unity rose from 20% to 80%, and scripting skills in C# improved from 25% to 75%. Knowledge of entrepreneurial concepts increased from 40% to 85%, and business planning skills rose from 25% to 80%. Conclusion: The program successfully enhanced both technical and entrepreneurial skills of Electronics Engineering graduates from SMK N 1 Bukittinggi, preparing them for the creative industry and enabling them to create their own business opportunities. This integrated approach can be applied to other vocational schools to support the growth of the local creative economy.